Adriano, i pitagorici e i misteri di morte e rigenerazione. Riflessioni sull’architettura romana tra 117 e 138 d.C. - Alessandra Randazzo (Papireto)
The emperor Hadrian (117 – 138 AD) is known for his contribution to Roman architecture characterized by an equilibrium between respect for tradition and innovation. This article will analyze the main architectural works, such as the Pantheon, the temple of Venus and Rome, Hadrian’s Villa (Tivoli) and the Mausoleum, promoted throughout his reign, highlighting how these landmarks not only reflect the architectural taste of the time but also Hadrian’s adherence to Pythagorean philosophy. Through the study of ancient literary sources, archeological data and the most recent historigraphical readings , it will reflect on how Hadrian used architecture to express his role as refounder of Rome, a Kosmocrator (ruler and builder of the world) and a Pythagorean scholar in the pursuit of harmony with the cosmos. The results highlight an exact correspondence between Pythagorean school precepts and the political and architectural expressions of this emperor. This study will, not only, contribute to a better understanding of Hadrianic architecture as the expression of imperial power, but also as necessary vehicle of philosophical communication and a new political ideology.